Heavy Metal (Pb) and Its Bioaccumulation in Red Algae (Gracilaria sp.) At Kupang Village, Jabon Sub-District, Sidoarjo District - Yatris Rambu Tega; Endang Yuli Herawati; Yuni Kilawati (Journal of Experimental Life Science)
Seaweeds have an inherent capacity to absorb heavy metals from marine water. This intrinsic ability allows these organisms to accumulate much amount of heavy metals over time. This study conducted at Kupang Village, Jabon Sub-District, Sidoarjo District, where almost 40% of the area consists of Gracilaria sp. ponds cultured. The purpose of this study was to analyze the Pb heavy metals concentration in water culture and its concentration in holdfast and thallus of Gracilaria sp. In this research, determination of samples in each pond was taken on day 0 (before planting), 20 days (Initial Production) and on day 40th (Post/Harvest). The aquatic parameters include salinity, temperature, acidity (pH), and dissolved oxygen (DO). Quantitative determination of heavy metals on sample using Atomic Absorption Spectrophotometry (AAS). Determinations of heavy metal accumulation in organism using Bioconcentratin factor (BCF) and Translocation factor was used to calculate the Pb heavy metal translocation process from the base to the tip of Gracilaria sp. The results of the study showed the highest Pb concentration found in the second sampling age 20 days, in pond 1 with 7.61 ± 0.18 mg.kg-1, and pond 2 was 5.35 ± 0.09 mg.kg-1. This concentration has not exceeded the threshold value that might have an effect if more than 8.6 mg.kg-1. The highest Pb level at the holdfast of Gracilaria sp. found at age 0 days before planting, which is 3.38 ± 0.23 mg.kg-1 and decreases to post-harvest (age of 40 days) which is 0.84 ± 0.00 mg.kg-1. The Transaction Factor (TF) of Pb heavy metal value from holdfast to thallus is 1,015 thus Gracilaria sp. absorbs heavy metals in high concentrations at the beginning of planting and is able to release it again before harvest time.